L’articulation de ressources mobilisées à différentes échelles dans les processus de reterritorialisation de l’alimentation - Marie Houdart; Virginie Baritaux; Vanessa Iceri; Sylvie Lardon; Salma Loudiyi (Développement Durable et Territoires)
The article focuses on the articulation of resources at different scales in the processes of reterritorialization of food. Eleven contrasting cases of collective actions are analyzed and compared. Two points are highlighted : reterritorialization relies on the mobilization and creation of territorial resources, which can be of different kinds ; it relies on territorial and extra-territorial resources, the latter being mobilized to initiate and sustain the action, to reinforce it, or to allow it to increase its scope. In particular, these results highlight the role of a multiplicity of actors in the transitions towards a more territorialized food system.